2019
DOI: 10.1038/s41598-019-54508-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of blood proinflammatory markers with psychological resilience and quality of life in civilian women with posttraumatic stress disorder

Abstract: Individuals with posttraumatic stress disorder (PTSD) show low resilience and impaired quality of life (QOL). Accumulating evidence shows that PTSD is associated with increased inflammation. Studies suggest that inflammation can be a key mechanism underlying low resilience/QOL, but this relationship has been understudied in individuals with PTSD. Here, we investigated the association of blood proinflammatory markers with self-reported resilience and QOL in civilian women with PTSD. Fifty-six women with PTSD an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…A recent study showed an increase of plasma TNF‐α and IL‐6 levels compared to healthy controls (Brahmajothi & Abou‐Donia, 2020), but other pro‐inflammatory cytokines are also upregulated in PTSD men and women (Hoge et al., 2009; see Figure 2a). Interestingly, a study conducted in Japanese PTSD women reported that increases in TNF‐α and IL‐6 blood levels were correlated with self‐reported resilience, while C‐reactive protein (CRP) was correlated with quality of life (Imai et al., 2019). Maladaptive responses of the peripheral immune system were also observed in MDD patients (Hodes, Kana, et al., 2015; Wohleb et al., 2016; see Table 3).…”
Section: Inflammation and Negative Emotional Behaviorsmentioning
confidence: 99%
“…A recent study showed an increase of plasma TNF‐α and IL‐6 levels compared to healthy controls (Brahmajothi & Abou‐Donia, 2020), but other pro‐inflammatory cytokines are also upregulated in PTSD men and women (Hoge et al., 2009; see Figure 2a). Interestingly, a study conducted in Japanese PTSD women reported that increases in TNF‐α and IL‐6 blood levels were correlated with self‐reported resilience, while C‐reactive protein (CRP) was correlated with quality of life (Imai et al., 2019). Maladaptive responses of the peripheral immune system were also observed in MDD patients (Hodes, Kana, et al., 2015; Wohleb et al., 2016; see Table 3).…”
Section: Inflammation and Negative Emotional Behaviorsmentioning
confidence: 99%
“…This might be due to their ability to maintain the balance of the intestinal microbiota, regulate the immunomodulatory responses as well as suppression of the potential pathogens, and the inhibition of carcinogenesis [ 12 , 16 , 17 ]. Since elevated inflammation and oxidative stress are associated with impairment of quality of life [ [20] , [21] , [22] , [23] , [24] ], thus, using synbiotics might be promising in improving the quality of life in patients with BCRL.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, lower levels of interleukin-6 (IL-6) and elevations of the chemokine CX3CL1 have been identified as potential markers of resilience (Imai et al, 2019;Zhang et al, 2020a). In a more general manner, research in animals has shown that exposure to social stress is associated with increase in levels of specific cytokines (IL-2, IL-6, IL-10, IL-17A, IL-22, and TNFα), and these changes are correlated with behavioral responses to stress, and these changes have been associated with reduced neurogenesis and synaptic plasticity (Hodes et al, 2014;Muhie et al, 2017).…”
Section: Immune-inflammatory Influences On Stress and Resiliencementioning
confidence: 99%
“…Changes in several inflammatory markers, such as elevations in C-reactive protein (CRP), lowered levels of the cytokines interferon-gamma (IFNγ) and tumor necrosis factor-alpha (TNFα), and elevated levels of the chemokines CCL13, CCL20, and CXCL6 have all been associated with an increased risk of PTSD following exposure to traumatic stressors ( Eraly et al, 2014 ; Michopoulos et al, 2020 ; Zhang et al, 2020a ). Conversely, lower levels of interleukin-6 (IL-6) and elevations of the chemokine CX3CL1 have been identified as potential markers of resilience ( Imai et al, 2019 ; Zhang et al, 2020a ). In a more general manner, research in animals has shown that exposure to social stress is associated with increase in levels of specific cytokines (IL-2, IL-6, IL-10, IL-17A, IL-22, and TNFα), and these changes are correlated with behavioral responses to stress, and these changes have been associated with reduced neurogenesis and synaptic plasticity ( Hodes et al, 2014 ; Muhie et al, 2017 ).…”
Section: Key Research Areas In the Neurobiology Of Resilience And Thementioning
confidence: 99%